2019
DOI: 10.1111/pai.13039
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotic treatment during pregnancy and infancy and the development of allergic diseases

Abstract: Background Allergies are a serious public health issue, and prevalences are rising worldwide. The role of antibiotics in the development of allergies has repeatedly been discussed, as results remain inconsistent. The aim of this study was to investigate the association between pre‐ and post‐natal antibiotic exposure and subsequent development of allergies (atopic dermatitis, food allergy, asthma, atopic sensitization and allergic rhinitis). Methods A total of 1080 children who participated in a European birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 30 publications
3
83
3
Order By: Relevance
“…Numerous experiments and epidemiologic data report an effect of the maternal microbiota, or of antibiotic treatment of the pregnant mother, on the immune system and susceptibility to inflammatory pathology of the offspring. 10,[20][21][22][23][24][25][26] During pregnancy, controversial evidence has suggested the existence of bacteria residing within the placenta, which could have an impact on the fetal immune system. 27,28 More likely, the microbiota of the pregnant mother produces compounds that affect the immune system of the fetus or the newborn (Fig.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…Numerous experiments and epidemiologic data report an effect of the maternal microbiota, or of antibiotic treatment of the pregnant mother, on the immune system and susceptibility to inflammatory pathology of the offspring. 10,[20][21][22][23][24][25][26] During pregnancy, controversial evidence has suggested the existence of bacteria residing within the placenta, which could have an impact on the fetal immune system. 27,28 More likely, the microbiota of the pregnant mother produces compounds that affect the immune system of the fetus or the newborn (Fig.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…To the editor, Prenatal antibiotic exposure has been suggested to be a risk factor for childhood allergic disease, possibly by affecting the development of a healthy and diverse microbiome, which is important for immune maturation. [1][2][3] Atopic dermatitis (AD) is often the first manifestation of the so-called "atopic march" and has a prevalence of over 10% among children in many developed countries. 4 We aimed to investigate the association between prenatal antibiotic exposure and AD at age 1 in the Japan Environment and Children's Study (JECS).…”
Section: No Association Between Prenatal Antibiotic Exposure and Atopmentioning
confidence: 99%
“…On the contrary, a European cohort study of 1080 children showed that parent-reported prenatal antibiotic use was associated with an increased risk of diagnosed or observed AD at age 1 year (aOR: 1.66, 95% CI: 1.11-2.48). 3 Additionally, a Danish birth cohort study of 62 650 mother-child pairs reported that prenatal antibiotic exposure increased the odds of developing AD at 18 months of age, which was consistent across different definitions of AD; however, this finding was only observed among children born from atopic mothers who used antibiotics in the first, second and third trimesters (aOR: 1.45, 95% CI: 1.19-1.76), which only accounts for <2% of the entire cohort. 2 A major limitation of our study is that we did not have sufficient data to assess the difference in the effect by the timing or dose of antibiotics used, as previously suggested 2,10 Furthermore, data were not available in our study to investigate the difference in the effect according to the type of systemic antibiotics used.…”
Section: No Association Between Prenatal Antibiotic Exposure and Atopmentioning
confidence: 99%
“…Several lines of evidence have indicated that dysbiosis in humans is associated with an increased prevalence of allergic sensitization 57,59,74-76 . However, the mechanisms underlying this association remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%